Awareness of heat transfer fluid degradation in thermal oil heater in Malaysia manufacturing industries - Mohd Mokhtar, Ahmad Fadzel; Mohd Mustafah, Anas (Science, Engineering and Health Studies, 2021)
A thermal oil heater (TOH) is a heating system that is preferred in the manufacturing industries. However, the potential risk for fire and explosion from thermal oil heaters has often been neglected. Heat transfer fluid (HTF) degradation is one of major issues when operating TOH because the degradation alters its physical properties. This paper aimed to evaluate the level of awareness of HTF degradation in TOH safety in Malaysia and to develop a baseline safety guideline on HTF degradation and TOH safety for Malaysian industries. Interviews were conducted and a questionnaire was developed to determine four elements: TOH safety, HTF of choice, HTF degradation and consequence, and preparedness for fire and explosion. The level of awareness of HTF degradation in TOH amongst the factories in Negeri Sembilan was found to be poor with the overall level of knowledge scores for TOH safety, HTF of choice, HTF degradation, and preparedness for fire and explosion. Finally, a baseline for safety guideline on HTF degradation and TOH safety was proposed and presented.